Evaluation of Science Learning with Teaching at the Right Level Approach: A Systematic Literature Review - Suriza Putri; Festiyed; Fatni Mufit (Program Studi Pendidikan Fisika, Universitas PGRI Semarang, 2025)
This study aims to assess the effectiveness of the Teaching at the Right Level (TaRL) approach in education through a systematic literature review. TaRL is a teaching method that is tailored to the individual abilities of learners. It ensures that every learner receives an education that is appropriate to their ability level. This review analyzed articles from academic journals published between 2018-2024, obtained through Google Scholar with the keywords “Teaching at the Right Level”, ‘TaRL’, and “learning evaluation”. The review was supported by the inclusion criteria of articles addressing the implementation and evaluation of TaRL, while opinion articles and unpublished reports were excluded. Based on the search results, 18 relevant articles were obtained. The results of the analysis show that the TaRL approach is effectively applied in science learning at the elementary, junior high and high school levels. This approach is proven to be able to improve learning outcomes, motivation, activeness, and communication skills of students. The success can be seen through various forms of evaluation and learning strategies that are systematically applied in the research cycle.